2012
DOI: 10.1186/1750-1172-7-s1-s6
|View full text |Cite
|
Sign up to set email alerts
|

Cherubism: best clinical practice

Abstract: Cherubism is a skeletal dysplasia characterized by bilateral and symmetric fibro-osseous lesions limited to the mandible and maxilla. In most patients, cherubism is due to dominant mutations in the SH3BP2 gene on chromosome 4p16.3. Affected children appear normal at birth. Swelling of the jaws usually appears between 2 and 7 years of age, after which, lesions proliferate and increase in size until puberty. The lesions subsequently begin to regress, fill with bone and remodel until age 30, when they are frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
200
0
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 159 publications
(213 citation statements)
references
References 93 publications
3
200
0
10
Order By: Relevance
“…From a psychological standpoint, early surgical intervention can have a very positive impact by preventing social ridicule and promote acceptance in the child's formative developmental years [7] . Furthermore, early tumor removal in the disease process, as advocated by the current report, could prevent any long-term sequelae requiring significantly more complex reconstructive surgery.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…From a psychological standpoint, early surgical intervention can have a very positive impact by preventing social ridicule and promote acceptance in the child's formative developmental years [7] . Furthermore, early tumor removal in the disease process, as advocated by the current report, could prevent any long-term sequelae requiring significantly more complex reconstructive surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, early tumor removal in the disease process, as advocated by the current report, could prevent any long-term sequelae requiring significantly more complex reconstructive surgery. Additionally, it has also been shown that early operation, with curettage during the growth phase can arrest the tumor growth, and not prompt rapid regrowth, thereby making it a favorable option in preventing further bony deformities [7,13,15,16] . Our report further strengthens this group of patients who have good outcomes with arrested tumor growth and excellent facial contouring following early surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations